Isotope effect on the detachment onset density in JET ohmic plasmas. (4th March 2020) - Solokha, V; Groth, M; Brezinsek, S; Brix, M; Corrigan, G; Guillemaut, C; Harting, D; Jachmich, S; Kruezi, U; Marsen, S; Wiesen, S
Abstract: This paper investigates the dependence of the detachment onset density on the hydrogen isotope species. In JET ohmic plasmas in the ITER-like wall (JET-ILW) materials configuration, the isotope effect is approximately 10%, and it was observed at the outer target only. The heavier isotopes exhibit lower detachment onset densities and density limits. In addition, higher subdivertor molecular pressures and divertor electron densities were observed in the deuterium (D) discharges compared to the hydrogen (H) discharges. EDGE2D-EIRENE and standalone EIRENE simulations show that lower conductance of the pumping plenum, scaling with m D / m H in the molecular flow regime present in the experiments, is the primary cause for the experimental observation.